The effect of using quantum teaching and motivation in learning toward students achievement - Zaroha Lenny; Firman Firman; Desyandri Desyandri (Jurnal Aplikasi IPTEK Indonesia, 2019)
This research is conducted based on low learning outcomes of students especially on science subjects.This research is conducted based on low learning outcomes of students especially on science subjects.The low learning outcomes of studentThe low learning outcomes of studentcan not be separated from the learning process that lasted for this.can not be separated from the learning process that lasted for this.One effort to overcome these problems is by usingthe Quantum Teaching strategy in learning.One effort to overcome these problems is by usingthe Quantum Teaching strategy in learning.The purpose of this study is to reveal the influence of Quantum Teaching strategy and students'motivation to increase the learning outcomes of science.The purpose of this study is to reveal the influence of Quantum Teaching strategy and students'motivation to increase the learning outcomes of science.This research used Quasi Experiment with 2x2 factorial design.This research used Quasi Experiment with 2x2 factorial design.The population in this study were students of class V at Gugus 1 Kecamatan Padang Barat Kota Padang.The population in this study were students of class V at Gugus 1 District of Padang Barat Kota Padang.The sample of this research was chosen by simple random sampling technique.The sample of this research was chosen by simple random sampling technique.Research data obtained from the results of test and questionnaire about students'motivation.Research data obtained from the results of test and questionnaire about students'motivation.Data analysis was done by using t-test technique.Data analysis was done by using t-test technique.The results showed that the science outcomes of students who were taught with Quantum Teaching strategies were better than the students who were taught by using conventional strategy.The results showed that the science outcomes of students who were taught with Quantum Teaching strategies were better than the students who were taught by using conventional strategy. Learning outcomes of students with high motivation who were taught with Quantum Teaching strategies are better than highly motivated learners taught by conventional strategy. The same thing shown that low-motivated learners who taught with Quantum Teaching strategies are better than low-motivated learners taught by conventional learning strategy.